Analisis Statistik Curah Hujan Terhadap Suhu dan Kelembapan di Provinsi Banten Tahun 2016-2024 - Rakha Mahardika Yudana; Tubagus Hafid; Angga Sutja Putra (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Rainfall is one of the climate elements influenced by various factors, including air temperature and humidity. Banten Province, with diverse geographical conditions, has varying rainfall patterns across its regions. This study aims to analyze the relationships between air temperature and humidity and rainfall in Banten Province during the 2016–2024 period using three statistical methods. Data were obtained from four stations of the Meteorology, Climatology, and Geophysics Agency (BMKG), namely the Climatology Station of South Tangerang, the Meteorology Station of Serang, the Meteorology Station of Curug, and the Geophysics Station of Tangerang, and were retrieved from the Central Statistics Agency (BPS). The analyses used include descriptive, multiple regression, and time-series analyses. The results of the descriptive analysis indicate diverse climate conditions across stations, with average air temperatures ranging from 27.04°C to 28.76°C, humidity ranging from 77.50% to 82.73%, and rainfall ranging from 115.51 mm/year to 194.87 mm/year. The multiple regression analysis results indicate that the influence of air temperature and humidity on rainfall is weak to moderate, with coefficient of determination values ranging from 11.46% to 54.61%. The time series analysis indicates a similarity in pattern between the predicted and actual rainfall values, with the highest degree of conformity found at the Meteorology Station of Curug. Overall, rainfall in Banten Province is fluctuating and influenced by the complexity of interactions among various natural climate factors.